2015
DOI: 10.1177/1535370215603837
|View full text |Cite
|
Sign up to set email alerts
|

Featured Article: Oxidative stress status and liver tissue defenses in diabetic rats during intensive subcutaneous insulin therapy

Abstract: Long-term insulin delivery can reduce blood glucose variability in diabetic patients. In this study, its impact on oxidative stress status, inflammation, and liver injury was investigated. Diabetes was induced in Wistar rats with a single dose of streptozotocin (100 mg/kg). Untreated rats and rats administered Insuplant Õ (2 UI/200 g/day) through a subcutaneous osmotic pump for one or four weeks were compared with non-diabetic controls. Body weight, fructosamine level, total cholesterol, Insulin Growth Factor-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…It would be interesting to determine whether patients in the non-controlled glycemia group had increased instances of intermittent hyperglycemia or whether it was sustained hyperglycemia. Animal studies have suggested that intermittent hyperglycemia has a more marked effect than sustained hyperglycemia in inducing oxidative stress and increasing inflammation; 44 however, studies in human adults have been less conclusive. Many studies in human adults have found no association between glucose variability and consequences of inflammation, such as microvascular or macrovascular complications, arterial stiffness, and carotid intimal thickness.…”
Section: Discussionmentioning
confidence: 99%
“…It would be interesting to determine whether patients in the non-controlled glycemia group had increased instances of intermittent hyperglycemia or whether it was sustained hyperglycemia. Animal studies have suggested that intermittent hyperglycemia has a more marked effect than sustained hyperglycemia in inducing oxidative stress and increasing inflammation; 44 however, studies in human adults have been less conclusive. Many studies in human adults have found no association between glucose variability and consequences of inflammation, such as microvascular or macrovascular complications, arterial stiffness, and carotid intimal thickness.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have suggested that intermittent hyperglycemia has a more pronounced effect than sustained hyperglycemia [10, 32, 33], although thus far human studies have been less convincing. We have previously found no relationship between glucose variability and endothelial function or endothelial progenitor cells in adolescents with T1D [29].…”
Section: Discussionmentioning
confidence: 99%
“…In adults with T1D, Buse et al [39] used sensor augmented pump therapy to reduce glucose variability in comparison to multiple daily injections and found a decrease in inflammatory ligand CD40L levels in the pump group but an increase in the injection group although the difference was not significant. In a single group study Dal et al [32] found no effect of flexible insulin therapy designed to reduce glucose variability although mean amplitude glucose excursion also did not change. Jamiolkowska et al [40] found that reducing glucose variability improved endothelial function in adolescents with T1D.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that even after glycemic control, oxidative stress continues to occur in diabetic patients, possibly due to metabolic memory, in which the oxidative modification of proteins and lipids leads to the propagation of oxidative stress (Costantino et al, 2017;Dal et al, 2015;Gadjeva et al, 2017;Rodrigues et al, 2018;Testa et al, 2017). Therefore, the phenolic compounds present in JPE become a possible adjuvant treatment to reduce the levels of oxidative stress, restore total leucocytes and lymphocytes, and modulate lipid levels in diabetic patients, to avoid related complications.…”
Section: F I G U R Ementioning
confidence: 99%
“…Free radicals are believed to play a major role in the onset and progression of late diabetic complications, due to their ability to damage lipids, proteins, and DNA (Ziegler, Buchholz, Sohr, & Roden, 2015). In addition, studies have shown that oxidative stress markers, such as reactive oxygen species (ROS) and lipid peroxidation, remains altered even after glycemic control in some diabetic patients (Dal et al, 2015;Gadjeva, Goycheva, Nikolova, & Zheleva, 2017;Rodrigues et al, 2018;Testa et al, 2017). Hence, studies have investigated the ability of phenolic compounds to prevent or decrease oxidative stress.…”
Section: Introductionmentioning
confidence: 99%